Risk factors for severity of thrombocytopenia in full term infants: a single center study - Amira M. Saber; Shereen P. Aziz; Al Zahraa E. Almasry; Ramadan A. Mahmoud (BMC, 2021)
Abstract Background Neonatal thrombocytopenia (NT) (platelet count < 150 × 109/L) is a common finding in the neonatal intensive care unit (NICU). The main aim of this study was to assess the prevalence, risk factors, and outcomes of severe NT in full term (FT) infants. Methods During the study period, all FT infants who met the inclusion criteria for NT on two occasions were included. Maternal data, such as maternal age, weight, gestational age, mode of delivery, and history of systemic diseases, including diabetes mellitus, pre-eclampsia, systemic lupus erythematosus, and immune thrombocytopenic purpura, were recorded. Furthermore, neonatal data, such as gender, neonatal weight, causes/duration of admission, types of respiratory support used, complete blood count measurements, and outcomes for neonates admitted to the NICU, were recorded. Results In total, 55 FT infants with NT met the inclusion criteria, and 29 (52.73%) cases had severe NT. The most common cause of NT was neonatal sepsis (20 cases, 36.35%), followed by a postoperative state (5 cases, 9.09%). Moreover, in cases of positive blood cultures, the most commonly isolated organism was Escherichia coli (6 cases, 10.90%), followed by Klebsiella (5 cases, 9.09%). Cases of severe NT needed more platelet transfusions (P = 0.001) and had higher rates of mortality (P = 0.001) when compared to cases of mild/moderate NT associated with signs of bleeding and pulmonary/intraventricular hemorrhage (IVH) (P = 0.001). Conclusion Severe NT compared to mild/moderate NT, associated with signs of bleeding and pulmonary/IVH, needed more platelet transfusions, and had increased mortality. Further research is needed to explain which of these complications related to severity of thrombocytopenia or were associated with original disease of the babies.